Management of Secondary Glaucoma after Pars Plana Vitrectomy (PPV) and Silicone Oil Injection in Rhegmatogenous Retinal Detachment - Muhammad Saleh Memon, Azizur Rahman, Asfandyar Asghar, Muhammad Nasir Bhatti, Tayab Shahzad (Pakistan Journal of Ophthalmology, 2010)
Purpose: To determine the outcome of secondary glaucoma after pars plana vitrectomy (PPV) and silicone oil injection in rhegmatogenous retinal detachment Materials and Methods: This Interventional quasi experimental study was conducted at Isra Postgraduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital, Malir, Karachi; from January 2006 to December 2007.Study included total 50 eyes of 50 patients fulfilling the inclusion criteria. After examination, patients were divided into three groups. Group -1 if IOP (intraocular pressure) from 22 mmHg up to 28 mmHg managed medically by anti-glaucoma drug like timolol 0.5% alone, group - II if IOP was raised over 28 mmHg than timolol 0.5% with dorzolamide 2% were prescribed and group – III if the patient’s IOP was not controlled medically, additional surgical intervention like silicone oil removal, diode cycloablation, cyclocryopexy and glaucoma valve surgery was performed. Success was defined as IOP ? 21 mmHg and ? 05 mmHg with or without medication. Patients were followed for 6 months. Results: Over follow up period of 6 months, successful IOP control was achieved in all 50 (100%) eyes. Conclusions: Glaucoma after PPV with silicone oil injection in rhegmatogenous retinal detachment can be effectively managed by anti-glaucoma medicines or with additional surgical measures.